2021
DOI: 10.33216/1998-7927-2021-267-3-124-127
|View full text |Cite
|
Sign up to set email alerts
|

Tourist enterprise marketing complex: international and national aspect

Abstract: The main features of the marketing complex for the enterprises of the tourist branch are considered in the article. In a market economy, the concept of marketing, as part of improving enterprise management, becomes an integral part of its activities. With the help of a number of controlled marketing variables, business entities can influence customers, stimulate them, encouraging them to certain, desirable for the company actions in the market until the purchase. One of the elements of the marketin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…O.В. Птащенко, et al focused on the analysis of tourism branch enterprises, mainly explored the characteristics of the marketing complex of tourism branch enterprises, discussed the branding elements of the marketing complex, and clarified that the purpose of marketing is to establish a longterm relationship with the consumer [13]. Rahman, M. S. et al found that little attention is currently paid to conceptualization of the analytical competence of the company's marketing and empirical investigation.…”
Section: Introductionmentioning
confidence: 99%
“…O.В. Птащенко, et al focused on the analysis of tourism branch enterprises, mainly explored the characteristics of the marketing complex of tourism branch enterprises, discussed the branding elements of the marketing complex, and clarified that the purpose of marketing is to establish a longterm relationship with the consumer [13]. Rahman, M. S. et al found that little attention is currently paid to conceptualization of the analytical competence of the company's marketing and empirical investigation.…”
Section: Introductionmentioning
confidence: 99%